How do team sports coaches debrief their players in elite sports? - Macquet, A. C.; Ferrand, C.; Stanton, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Debriefing is both a process, namely the way debriefing is prepared and transmitted to players, and a product, namely the message transmitted to players. It has potential positive outcomes on learning, motivation, confidence, emotional recovery, and reflectivepractice. To date, there are few studies on debriefing in sport. The present study aimed to explore the process used by staff to prepare and transmit debriefing in elite team sports as well as explore the content of debriefing. Method: Nine national coaches of basketball, volleyball, handball, field and ice hockey volunteered to participate in the study. Data collection involved semi-structured interviews with each participant separately. Coaches were asked to explain how they prepared and transmitted their debriefings to players in major competitions. Data processing involved inductive and deductive analysis of verbal reports. Results: Results showed that debriefing consisted of two parts: preparing for the game assessment, and transmitting the game assessment and fostering players` involvement in the following match. Preparing for the game assessment involved: (a) preparation of video material (i.e., recovering the video of the match and sequencing it); (b) assessment of own team`s game (i.e., strengths and weaknesses, efficiency of game plan and game plan implementation, performance statistics, possible causes of achievements and failures, areas for improvement); (c) development of presentation material (i.e., most meaningful video sequences, players` feelings and analysis); and (d) division of labor. Transmitting the game assessment and fostering players` involvement in the following match comprised: (a) encouraging players to analyze their own game and transmitting assessments of the game (i.e., efficiency of game plan implementation, areas for improvement, taking into account players` attention capabilities); (b) fostering players` involvement in the following match (i.e., stressing the work done, boosting players` confidence and motivation, managing substitutes` frustration and players` roles, turning the page on the game and think about recovery and following match). Discussion: Results suggest that debriefing involves tactical as well as psychological work. Tactical work relates to the work done. Psychological work consists of players` attitudes, commitment and motivation. They are both influenced by what went well and badly in the past in order to highlight what needs to be done in the immediate future. Results also suggest that the work of debriefing was divided according to staff and players` roles, competencies and experience. Results have been used to improve communication between the coach and players and enhance team performance